EDUCATIONAL EMPOWERMENT AND USE OF ANTENATAL SERVICES - Muhammad Siddique Khan Qadr; Huda Abbas; Wajahat Hussain et al. (Journal of University Medical & Dental College, 2019)
ABSTRACT:OBJECTIVE: The single most important factor that has long-lasting impact on lives of women is education. The study was conducted to determine the eﬀect of women and partner's education on utilization of antenatal services in the urban slums.STUDY DESIGN AND SUBJECTS: This descriptive cross sectional study was conducted in urban slums of Bahawalpur City from January 2018 to December 2018 after taking ethical approval from hospital ethical committee. Women of reproductive age n=377, between 15 to 49 years, having at least one alive child less than one year of age and irrespective of current pregnancy were included in the study. Out of selected slum area sample was drawn by non-probability consecutive method. The preformed, pretested questionnaire with the help of lady health workers of the areas was used for collection of data.RESULTS: Mean age of the respondents was 28.26 ± 6.03 years. The age distribution showed that 31.1% respondents belonged to 30-34 years age group followed by 29.7% in 25-29 years, 19.1% in 20-24 years. The utilization of antenatal services was poor in 41.1% (n=155), fair in 24.9% (n=94) and good in 34.0% (n=128) women. The utilization of antenatal services was signiﬁcantly higher in literate group (p <0.001). Regarding husband's educational status the wives of educated husbands had better utilization (p <0.001). The use of antenatal services among wives of uneducated and primary educated husbands was 67.8% and 61.5% respectively. The 52.1% women having graduate and above educational level of husband had good antenatal care use.CONCLUSION: Educational status signiﬁcantly aﬀect the utilization of antenatal services.